The horizon of wonder: perseverance, surprise and appeasement in the phenomenology of perception - Verissimo, Danilo Saretta [UNESP] (FapUNIFESP (SciELO), 2025)
The phenomenology of perception favors attitudes of wonder, perseverance, tolerance to indetermination, openness to surprise and inquiry, and appeasement of our need to perceive everything while highlighting our early adherence to things and the objectivist aspiration that permeates our social practices. This article examines the key terms of this condition of receptivity and criticism. Stability of the perceptual field is associated with its transformational nature, unveiling the existential character of perception and its affects. In this regard, we raised psychosocial issues based on Husserl’s description of the structure of horizons of perception. The temporality of perception stands out, guided by expectations and the unexpected. From there, we discuss anticipation in perception, the possibility of wonder, and the phenomenon of surprise. We close with epistemological and social considerations on ways of denying the indeterminacy of sensitive experience.
El horizonte del asombro: perseverancia, sorpresa y apaciguamiento en la fenomenología de la percepción
L’horizon de étonnement: persévérvance, surprise et apaisement dans la phénoménologie de la perception
Keywords: anticipation; expectation; Husserl; perception; phenomenology